Concurrent Authority in Regional Government Relating to the Health Sector Based on Indonesian Regulations - Mongkaren, Ciendy Meilanda Ivo (Journal of The Community Development in Asia, 2024)
This study supports analyzing health decentralization from three factors: authority, regional resources, and access. The research method used is by normative legal research examines law that is conceptualized as an applicable norm. The results of the study show how the implementation of concurrent affairs health decentralization in North Sulawesi and East Bolaang Mongondow regency is as follows: Low regional capacity characterized. Research indicates that concurrent authority in Indonesia’s decentralized health sector is governed by Law Number 23 of 2014. This law delineates responsibilities among the central government, provincial government, and city district governments in managing four specific health-related matters. The legal foundation aligns with constitutional recognition of health as a fundamental human right, as outlined in Law Number 39 of 1999 and the International Covenant on Economic, Social and Cultural Rights (Law Number 11 of 2005). To optimize health services, stakeholders are urged to collaboratively implement concurrent authority efficiently. This synergy, grounded in legal frameworks and human rights principles, promises to advance the realization of an adequate standard of living and the highest attainable health standards for all Indonesians.